Clinical InvestigationsA study on the variation of bladder and rectal doses with respiration in intracavitary brachytherapy for cervix cancer - Prabhakar, Ramachandran; Jagadesan, Pandjatcharam; Haresh, Kunhi P; Karuna, Singh; Julka, Parmod Kumar; Rath, Goura Kisor (Journal of Contemporary Brachytherapy, 2010)
Purpose: In cervical intracavitary brachytherapy, it is mandatory to evaluate if the doses to bladder and rectum are within tolerance limits. In this study, an effort has been made to evaluate the effect of respiration on the doses to bladder and rectum in patients undergoing brachytherapy. Material and methods: Fifteen patients with cervix cancer treated with concurrent chemoradiation followed by intracavitary brachytherapy were included in this study. At the time of brachytherapy, all patients underwent 4D computed tomography (CT) imaging. Five out of fifteen patients were scanned with empty bladder while the rest had full bladder during sectional imaging. Four sets of pelvic CT image datasets with applicators in place were acquired at equal interval in a complete respiratory cycle. Treatment plans were generated for all the CT datasets on a PlatoTM Sunrise planning system. A dose of 7 Gy was prescribed to Point A. Doses to ICRU (Report No.38) bladder (IBRP) and rectal (IRRP) reference points were calculated in all the CT datasets. Results: The mean of maximum dose to IBRP at four different respiratory phases for full and empty bladder were 53.38 ± 19.20%, 55.75 ± 16.71%, 56.13 ± 17.70%, 57.50 ± 17.48% and 60.93 ± 15.18%, 60.29 ± 16.28%, 60.86 ± 15.90%, 60.82 ± 15.42% of the prescribed dose respectively. Similarly, maximum dose to IRRP for full and empty bladder were 55.50 ± 18.66%, 57.38 ± 14.81%, 58.00 ± 14.97%, 58.38 ± 17.28% and 71.96 ± 6.90%, 71.58 ± 7.52%, 68.92 ± 6.21%, 71.45 ± 7.16% respectively. Conclusions: Our study shows that respiration affects the dose distribution to the bladder and rectum in intraca-vitary brachytherapy of cervix cancer. It is advisable to reduce the critical organ dose to account for the dose variation introduced by respiratory motion.